Komunikasi Bijak Sebagai Metode Dalam Penyelesaian Konflik - Dina Kristina (STAI Bumi Silampari, 2025)
This study explores “wise communication” as a systematic method in resolving interpersonal and group conflicts. The main objective is to formulate key elements of wise communication and test its effectiveness in reducing conflict escalation and reaching mutual agreement. The findings of this study discuss the importance of having social awareness and moral awareness of each individual and element of society in order to communicate wisely as an effort to resolve and prevent conflict to create a peaceful and harmonious social life. The method used is the library method. Based on the results of the study, in principle, wise communication will pay attention to moral and ethical values ??in conveying messages. The message giver must also be able to appropriately and position themselves in speaking and behaving, namely paying attention to words that are appropriate to be conveyed, paying attention to who the message will be conveyed and most importantly having the appropriate time and place to convey the message. The study concludes that wise communication is not just a verbal technique, but a value framework that combines caution and moral assertiveness. Practical recommendations include empathy training and structured dialogue facilitation for mediators, community leaders, and human resource practitioners.